Processing and dry sliding wear behavior of Al2O3 nanoparticles reinforced ZA-27 composites. (2017) - Shivakumar, N.; Vasu, V.; Narasaiah, N.
Abstract: ZA-27 nanocomposites is very promising material, which are suitable for a large number of applications. These nanocomposites consists of a metal matrix with nano-particles to improve the mechanical properties and wear resistance compare to the base material.ZA-27 alloy and composites reinforced with aluminium oxide (Al2 O3 ) nanoparticles, ranging from 1, 2 and 3 weight percentage (wt%) are fabricated by using stir casting followed by ultrasonic assisted casting method. Microstructure analysis of alloy and nanocomposites were examined by using Optical Microscope (OM).Dry sliding wear is measured on Pin-on-Disc testing apparatus, at various testing conditions for alloy and nanocomposite materials. Morphology study of the wear samples are also carried out by using Optical Microscope (OM). From the results, it's observed that, as the wt% of the reinforced Al2 O3 nanoparticles increases, the wear resistance increases.